KARAKTERISASI MINYAK IKAN DARI HASIL SAMPING INDUSTRI PENEPUNGAN IKAN LEMURU (Sardinella lemuru) DENGAN METODE PEMURNIAN ALKALI - Ibrahim, Bustami; Suptijah, Pipih; Yogaswara, Ghema (Dinamika Maritim, 2015)
Utilization of fish Lemuru ( Sardinella lemuru ) into fish meal has a byproduct in the form of fish oil . It is known that the content of omega-3 fatty acids in fish oil lemuru highly enough . So that the existing oil content in fish processing waste of lemuru needs to be recovered by purification , so that fish oil obtained has better quality . In this study, fish oil is purified by the alcaline refining methode . The result of the process of purifying fish oils have a better quality than that of unrefined fish oil . But the content of saturated fatty acids to decrease. The quality of fish oil purified with alcaline methode and purification done by the plant were not significantly different